1974
DOI: 10.1002/1097-0142(197402)33:2<446::aid-cncr2820330221>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The value of staging laparotomy in non-Hodgkin's lymphomas.(With emphasis on the histiocytic type)

Abstract: Laparotomy with splenectomy and multiple tissue biopsies was performed in 106 adult patients with non‐Hodgkin's lymphoma (histiocytic—76, lymphocytic—25, and mixed type—5). The histologic pattern at initial biopsy showed nodular lymphoma in 33% and diffuse lymphoma in 67%. Diffuse histiocytic was the most frequently observed histologic type in this series (54%). Before laparotomy, 92% of patients had primary lymphatic and 8% primary extralymphatic involvement. Waldeyer's ring involvement accounted for 27% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Literature data indicate that the presence of lymphoma in the liver practically always means that the spleen is involved as well (9,17). We confirmed this finding: all patients with proven hepatic involvement, from whom splenic tissue was available, also demonstrated splenic involvement (Table 3).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Literature data indicate that the presence of lymphoma in the liver practically always means that the spleen is involved as well (9,17). We confirmed this finding: all patients with proven hepatic involvement, from whom splenic tissue was available, also demonstrated splenic involvement (Table 3).…”
Section: Discussionsupporting
confidence: 83%
“…5 5~ splenic index (16). Thus an index of 480 as upper limit for normal size (13) corresponds to a weight of 265 g. Several other studies revealed that a splenic weight of more than 500 g consistently implied splenic involvement (8,10,17). It was calculated that weight determination using a weight of 500 g as threshold value would result, for the present series, in an accuracy of 77 per cent, a specificity of 100 per cent and a sensitivity of 72 per cent.…”
Section: Discussionsupporting
confidence: 44%
“…Histologic subtypes according to the Japanese literature are summarized in the categories of diffuse large cell, lymphoblastic, diffuse small cell and diffuse mixed and lymphoblastic PSL. Concomitant immunohistochemical subdivision of malignant PSL seems to determine associated prognosis and therapeutic outcome [22]. Ahmann classifi ed the gross pathological appearance of primary lymphomatous involvement of the spleen into 4 categories including homogenous enlargement without masses, miliary masses, 2-10 cm neoplasms and a large solitary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with malignant lymphoma (HD and NHL), subjected to staging laparotomy, the spleen is found to be histologically involved in 23 to 50 per cent of cases (3,5,6,9,10,12,14,17). Although the incidence of splenic involvement increases with increasing weight of the specimen, there is no absolute correlation between weight as measured after splenectomy and histologic state.…”
Section: Discussionmentioning
confidence: 99%